ANALISIS FAKTOR RISIKO PENURUNAN FUNGSI KOGNITIF PADA LANSIA DENGAN DIABETES MELITUS - Ernita, Ernita; Dg. Masikki, Maharani Farah Dhifa; Arifin, Hasriany; Dharmawan, Rio L.; Rofiqoh, Rofiqoh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on an initial survey in the Makmur Village of the Pangkalan Kerinci II BLUD Puskesmas Working Area of 8 elderly DM, it was found that the elderly often forgot when putting their own things, forgot the day, date and even often forgot what was just discussed, 5 elderly people did not remember the elderly posyandu schedule or blood sugar control schedule. The purpose of the study was to determine the relationship between risk factors for decreased cognitive function in the elderly with diabetes mellitus. This type of research uses quantitative with a cross sectional approach. The research was conducted in June 2023 using total sampling. The sample amounted to 167 people. The results showed that there was a relationship between family support (p value: 0.001) and physical activity (p value: 0.000) on the decline in cognitive function in the elderly with DM. It is recommended to the Puskesmas to increase elderly Posyandu activities and make health promotion efforts to DM sufferers and families. Keywords: Diabetes, Family Support, Elderly.